2020
DOI: 10.18632/oncotarget.27400
|View full text |Cite
|
Sign up to set email alerts
|

A pan-cancer transcriptome analysis identifies replication fork and innate immunity genes as modifiers of response to the CHK1 inhibitor prexasertib

Abstract: The combined influence of oncogenic drivers, genomic instability, and/or DNA damage repair deficiencies increases replication stress in cancer. Cells with high replication stress rely on the upregulation of checkpoints like those governed by CHK1 for survival. Previous studies of the CHK1 inhibitor prexasertib demonstrated activity across multiple cancer types. Therefore, we sought to (1) identify markers of prexasertib sensitivity and (2) define the molecular mechanism(s) of intrinsic and acquired resistance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 56 publications
2
18
0
Order By: Relevance
“…35 Recently, prexasertib-mediated acquired resistance is reported to be associated with components of innate immunity in a panel of pancancer cell line models and in vivo carcinoma and sarcoma models. 39 In our study, we also provide evidence that prexasertib-mediated acquired resistance is, at least in part, due to immune evasion. In the expression data, we observed increased expression of several immunosuppressive regulatory genes including Foxp3, Icos, Gitr, Ccr2, and xasertib resulted in treatment-related adverse events including neutropenia, leukopenia, anemia, thrombocytopenia, and fatigue.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…35 Recently, prexasertib-mediated acquired resistance is reported to be associated with components of innate immunity in a panel of pancancer cell line models and in vivo carcinoma and sarcoma models. 39 In our study, we also provide evidence that prexasertib-mediated acquired resistance is, at least in part, due to immune evasion. In the expression data, we observed increased expression of several immunosuppressive regulatory genes including Foxp3, Icos, Gitr, Ccr2, and xasertib resulted in treatment-related adverse events including neutropenia, leukopenia, anemia, thrombocytopenia, and fatigue.…”
Section: Discussionsupporting
confidence: 61%
“…To date, several mechanisms of prexasertib resistance have been published including but not limited to mutations in the target gene, activation of compensatory signaling pathways, and immune evasion 38 . Recently, prexasertib‐mediated acquired resistance is reported to be associated with components of innate immunity in a panel of pan‐cancer cell line models and in vivo carcinoma and sarcoma models 39 . In our study, we also provide evidence that prexasertib‐mediated acquired resistance is, at least in part, due to immune evasion.…”
Section: Discussionmentioning
confidence: 99%
“…Here, we demonstrated the impact of differences in CDK1 activity regulated by an MMB-FOXM1-dependent feedback loop in triggering replication catastrophe after CHK1 inhibition. LIN54 and FOXM1 were separately shown to modulate CHK1i sensitivity in ovarian and pancreatic cancer, respectively ( Blosser et al, 2020 ; Chung et al, 2019 ). This result suggests that the insights about the S/G2/M transition derived from this study could inform the use of CHK1is in additional cancer types.…”
Section: Discussionmentioning
confidence: 99%
“…Monotherapy with the CHK1 inhibitor (CHK1i) prexasertib has shown safety and tolerability ( Hong et al, 2016 , 2018 ). Prexasertib and CHK1 depletion have little to no effect on non-transformed cells such as RPE-1, whereas CHK1i mono-therapy exhibits activity in multiple cancer cell lines ( Blosser et al, 2020 ; Cole et al, 2011 ; King et al, 2015 ; Koppenhafer et al, 2018 ). However, intrinsic or acquired resistance to CHK1i may limit clinical efficacy.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, it has been reported that the acquired resistance of prexasertib is associated with innate immunity [167,168]. Blosser et al [168] identified the correlation between prexasertib resistance with innate immunity genes and described the association between the sensitivity of prexasertib and the expression of E2F target genes. The expression of immune-related and E2F/ G2M/SAC genes contributes to prexasertib resistance.…”
Section: Resistance To Chk1 Inhibitorsmentioning
confidence: 99%